Increasing Community Income Through Utilization of Rambutan and Lemon Skin as Antioxidant Herbal Tea in Binjai, North Sumatera: Peningkatan Pendapatan Masyarakat Melalui Pemberdayaan Kulit Rambutan dan Lemon Sebagai Teh Herbal Antioksidan Di Binjai, Sumatera Utara - Suci Nasution, Embun; Fauzan Lubis, Muhammad; Fajar Putra, Adika (Universitas Haji Sumatera Utara, 2025)
Rambung Dalam is one of the sub-disctrict on Jalan Padang, South Binjai, Binjai city, North Sumatera, Indonesia. Rambung Dalam sub-district faces a specific issue, which is the suboptimal utilization of the potential natural resource (rambutan peel waste), where rambutan itself is one of the region's distinctive natural resources. This ommunity aims to provide education about branding of pharmacist, utilization of rambutan and lemon peel as antioxidant tea and workshops on making it, as well as marketing and business plans for a product. The community service was conducted on August 8, 2024 using a modified Community Based Interactive Approach (CBIA) method. This activity was divided into three stages, pre-implementation, implementation, and monitoring and evaluation stages. The formula of antioxidant herbal tea using dried rambutan and lemon peel introduced to the community had been evaluated based on organoleptic tests, antioxidant activity tests, and yeast and mold count tests. The organoleptic test results with 1:1 formula yielded a tea infusion with a brownish-orange color, slightly bitter taste, and strong herbal aroma. The antioxidant test using 2,2- azinobis-3-Ethylbenzothiazoline-6-Sulfonic Acid with three repetitions showed an average IC50 value of 147.63 ppm, categorized as moderate antioxidants. The yeast and mold count test results showed 227 colonies/gram of tea (fulfill the requirement). The participants include community representatives, farmers, housewives, Integrated Healthcare Center staff, youth organizations, and community members actively involved during the activities. The community service using the CBA method can increase the knowledge and skills of participants by 72%, determined from pre-test and post-test results